Job satisfaction, affective commitment, and turnover intentions among front desk staff: evidence from Pakistan - Mehmood, Nasir (Econjournals, 2016)
Understanding attitudes and behaviors at workplace develop organizational knowledge and capabilities to increase quality of services and help in retaining competent and skillful employees. The present study aims to investigate the relationship between job satisfaction (JS), affective commitment (AC), and turnover intentions (TI) among front desk staff working as customer service representatives in Pakistani banks. Data was collected through questionnaire from 106 front desk customer representatives in 5 different banks located in Rawalpindi district of northern Punjab, Pakistan. Correlation and regression analysis concluded that both, JS and AC, were significantly related to the TI with negative associations. Based on the conclusions of this study, the implications for future studies are discussed.